ACE inhibitors, statins and thiazides: no association with change in grip strength among community dwelling older men and women from the Hertfordshire Cohort Study. - Witham, MD; Syddall, H; Dennison, E; Cooper, C; McMurdo, M; Sayer, A (Oxford University Press, 2014)
BACKGROUND: vascular disease has been postulated to contribute to muscle dysfunction in old age. Previous studies examining the effects of cardiovascular drugs on muscle function have shown conflicting results. We therefore examined the association of angiotensin converting enzyme (ACE) inhibitor, thiazide and statin use with decline in grip strength in a well-characterised cohort. METHODS: we analysed prospectively collected data from the Hertfordshire Cohort Study (HCS). For each medication, participants were divided into no baseline use/no use at follow-up, baseline use/no use at follow-up, no baseline use but use at follow-up and use at baseline and follow-up. For each group, annualised decline in grip strength (kg per year) was calculated, then adjusted for baseline age, height, weight, baseline grip strength, indices of ischaemic heart disease and hypertension. Analyses were conducted separately for males and females. RESULTS: 639 participants were included in the analysis, mean age 65 years. 321 (50%) were male; mean follow-up time was 4.4 years. There were no differences in baseline grip between baseline users and non-users of any drug class. Adjusted grip strength change per year was similar for each group of ACE inhibitor use (P > 0.05). Similar analyses revealed no significant between-group differences for statin or thiazide use. Analysis of dropout rates by medication use revealed no evidence of selection bias. CONCLUSION: use of ACE inhibitors, statins or thiazides was not associated with differences in grip strength decline in healthy older people in the HCS.